Ability of leaf mesophyll to retain potassium correlates with salinity tolerance in wheat and barley - Wu, Honghong; Shabala, Lana; Barry, Karen; Zhou, Meixue; Shabala, Sergey (Physiologia plantarum, 2013)
This work investigated the importance of the ability of leaf mesophyll cells to control K+ flux across the plasma membrane as a trait conferring tissue tolerance mechanism in plants grown under saline conditions. Four wheat (Triticum aestivum and Triticum turgidum) and four barley (Hordeum vulgare) genotypes contrasting in their salinity tolerance were grown under glasshouse conditions. Seven to 10‐day‐old leaves were excised, and net K+ and H+ fluxes were measured from either epidermal or mesophyll cells upon acute 100 mM treatment (mimicking plant failure to restrict Na+ delivery to the shoot) using non‐invasive microelectrode ion flux estimation (the MIFE) system. To enable net ion flux measurements from leaf epidermal cells, removal of epicuticular waxes was trialed with organic solvents. A series of methodological experiments was conducted to test the efficiency of different methods of wax removal, and the impact of experimental procedures on cell viability, in order to optimize the method. A strong positive correlation was found between plants' ability to retain K+ in salt‐treated leaves and their salinity tolerance, in both wheat and especially barley. The observed effects were related to the ionic but not osmotic component of salt stress. Pharmacological experiments have suggested that voltage‐gated K+‐permeable channels mediate K+ retention in leaf mesophyll upon elevated NaCl levels in the apoplast. It is concluded that MIFE measurements of NaCl‐induced K+ fluxes from leaf mesophyll may be used as an efficient screening tool for breeding in cereals for salinity tissue tolerance.